2021
DOI: 10.1029/2020pa004033
|View full text |Cite
|
Sign up to set email alerts
|

A 1 Million Year Record of Biogenic Silica in the Indian Ocean Sector of the Southern Ocean: Regional Versus Global Forcing of Primary Productivity

Abstract: The oceanic and atmospheric components of the global carbon cycle are directly linked through photosynthesis and the export of marine organic matter to the deep ocean, remineralization, and upwelling of respired carbon back into the atmosphere. The Antarctic Zone of the Southern Ocean, where deep waters upwell on the large scale, thus plays an important role in ocean-atmosphere CO 2 transfer and hence glacial to interglacial-scale climate change (e.g., Sigman & Boyle, 2000). As reviewed in detail recently by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Recent studies have highlighted that orbital forcing played a substantial role in the changes in AMOC, SO windstress, and SO ventilation during the last deglaciation [76]. Additionally, the authors of [77] provided evidence of orbital-scale changes in the wind-driven SO upwelling. This study shows that the ORB experiment followed the FULL experiment simulated SO upwelling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have highlighted that orbital forcing played a substantial role in the changes in AMOC, SO windstress, and SO ventilation during the last deglaciation [76]. Additionally, the authors of [77] provided evidence of orbital-scale changes in the wind-driven SO upwelling. This study shows that the ORB experiment followed the FULL experiment simulated SO upwelling.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [75] showed that the SH orbital forcing changes, and Antarctic sea ice feedback influenced the SO climate during the last deglaciation. Recent studies have also highlighted the role of orbital forcing in wind-driven SO upwelling [76,77]. This modeling study investigates the response of orbital and meltwater climate forcings to the SO dynamics during the last deglacial period from 19 to 9 kyr BP.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by a wholesale slowdown in nutrient supply or a shift in the locus of nutrient consumption and the advection of the nitrogen isotopic signature of enhanced consumption northwards. Intermittent increases in biogenic opal accumulation occur in the SAZ after 900 ka and after 400 ka in the Antarctic Zone perhaps suggesting a progressive southward shift in productivity (Figure 5) (Billups et al., 2018; Diekmann & Kuhn, 2002; Kaiser et al., 2021). Our observation supports a more polar Southern Ocean driver, whether biological or physical, of carbon sequestration during late MPT glacials.…”
Section: Discussionmentioning
confidence: 99%
“… Opal mass accumulation rates (mg/cm 2 /Kyr) from the (a) Subtropical frontal zone, IODP Site U1475; (b) Subantarctic Zone, ODP Site 1090 (Diekmann & Kuhn, 2002); (c) Antarctic Zone, ODP Site 745B (Billups et al., 2018; Kaiser et al., 2021) showing a southward shift in the relative, site specific, magnitude of biogenic opal deposition within the Southern Ocean around the Mid‐Pleistocene Transition. Bold lines show a 10 Kyr kernel smoothing.…”
Section: Datamentioning
confidence: 99%
“…For spectral analysis on individual time intervals, we used 90 lags and a confidence interval of 95%. Evolutive spectra were conducted on the entire 2.6 myr long record afforded by appending the late Pleistocene opal record from Kaiser et al (2021). Analyses were conducted using the Acycle software package by Li et al (2019).…”
Section: Time Series Analysismentioning
confidence: 99%